2020
DOI: 10.1039/d0py00308e
|View full text |Cite
|
Sign up to set email alerts
|

Self-crosslinking smart hydrogels through direct complexation between benzoxaborole derivatives and diols from hyaluronic acid

Abstract: By tailoring the structure of benzoxaborole (BOR), self-crosslinking hydrogels based on hyaluronic acid (HA) modified with BOR derivatives are obtained for the first time through the direct BOR-HA diol complexation at physiological pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…This study showed that the resulting partially fluorinated material had a higher dynamic modulus and a faster relaxation time than the non-fluorinated analog. 236 Figure 16. Synthesis of a network based on boronic esters a. polyethylene glycol (PEG) monomers functionalized by boronic acids (blue) and diols (red) and their equilibrium with the boronic ester form b. schematic representation of the network.…”
Section: -228mentioning
confidence: 99%
“…This study showed that the resulting partially fluorinated material had a higher dynamic modulus and a faster relaxation time than the non-fluorinated analog. 236 Figure 16. Synthesis of a network based on boronic esters a. polyethylene glycol (PEG) monomers functionalized by boronic acids (blue) and diols (red) and their equilibrium with the boronic ester form b. schematic representation of the network.…”
Section: -228mentioning
confidence: 99%
“…Hyaluronan itself contains diols, which may form additional complexes with boronic acids to stabilize the gel, as suggested by the complexation of benzoxaborole derivatives and hyaluronic acid diols at physiological pH. [ 20 ] However, the slower gelation precludes cell encapsulation in aqueous environments. In contrast, a fast gelling hydrogel of HA modified with phenylboronic acid (PBA) and poly(vinyl alcohol) (PVA) enabled 3D culture of neural progenitor cells.…”
Section: Case Studies Of 3d Cell Culture In DCC Hydrogelsmentioning
confidence: 99%
“…Dynamic covalent bonds are reversible chemical bonds which can break and reform on time scales relevant for cell‐based matrix remodeling, an important feature for 3D culture. [ 17 ] Specific examples of DCC which have been tailored to be compatible with 3D cell culture include boronate ester, [ 18–23 ] hydrazone, [ 24–30 ] Diels‐Alder, [ 31–37 ] oxime, [ 38–43 ] thiol–disulfide exchange, [ 44–46 ] and imine crosslinking. [ 17,47,48 ] These crosslinking methods can be performed at physiological pH and temperature, are fast reacting, and their reaction kinetics can be tailored to achieve a wide range of viscoelastic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Some key factors for the formation of the boronic ester bonds include the binding affinity of the boronic acid derivate towards the diol (Ka), their pKa, and the pH of the medium. The optimal pH for the formation of the ester bond can be found between the pKa values of boronic acid and the diol [37][38][39][40]. The estimation was proposed by "the charge rule": "sum of the charges of the free esterifying species is equal to the charge of the ester" [41].…”
Section: Boronic-ester Formationmentioning
confidence: 99%